Crowdfunding for health research: a qualitative evidence synthesis and a pilot programme. Issue 7 (27th July 2022) - Kpokiri, Eneyi Edith; Sri-Pathmanathan, Clarisse; Shrestha, Priyanka; Navaid, Sana; Wiwatpanit, Teerawat; Wijegunawardana, Asha; Ali Umar, Mahmud; Jackson, Debra; Alger, Jackeline; Bohren, Meghan A; Hoole, Mia; Labarda, Meredith; et al.
Abstract : Background: Many low-income and middle-income country (LMIC) researchers have disadvantages when applying for research grants. Crowdfunding may help LMIC researchers to fund their research. Crowdfunding organises large groups of people to make small contributions to support a research study. This manuscript synthesises global qualitative evidence and describes a Special Programme for Research and Training in Tropical Diseases (TDR) crowdfunding pilot for LMIC researchers. Methods: Our global systematic review and qualitative evidence synthesis searched six databases for qualitative data. We used a thematic synthesis approach and assessed our findings using the GRADE-CERQual approach. Building on the review findings, we organised a crowdfunding pilot to support LMIC researchers and use crowdfunding. The pilot provided an opportunity to assess the feasibility of crowdfunding for infectious diseases of poverty research in resource-constrained settings. Results: Nine studies were included in the qualitative evidence synthesis. We identified seven findings which we organised into three broad domains: public engagement strategies, correlates of crowdfunding success and risks and mitigation strategies. Our pilot data suggest that crowdfunding is feasible in diverse LMIC settings. Three researchers launched crowdfunding campaigns, met their goals and received substantial monetary (raising a total of US26 546 across all three campaigns) and non-monetary contributions. Two researchers are still preparing for the campaign launch due to COVID-19-related difficulties. Conclusion: Public engagement provides a foundation for effective crowdfunding for health research. Our evidence synthesis and pilot data provide practical strategies for LMIC researchers to engage the public and use crowdfunding. A practical guide was created to facilitate these activities across multiple settings.